DIAGNOSTIC OF NONSECRETORY MULTIPLE MYELOMA (CLINICAL CASE) - N. T. Vatutin; N. S. Kovalenko; E. V. Sklyannaya; A. N. Zagoruiko; M. A. El-Khatib; S. V. Starcenko; M. V. Makarova; I. G. Lozhechnyk (SINAPS LLC, 2017)
The article presents a clinical case of nonsecretory multiple myeloma, verified with immunohistochemical staining. It was hard to prove the diagnosis as the patient had extramedullar lesions adding to the bone destructions, the bone marrow was minimally infiltrated with plasma cells, ESR was normal, no monoclonal protein was present in the serum and urine.